Unreal Engine game development cookbook : over 40 recipes to accelerate the process of learning game design and solving development problems using Unreal Engine /: over 40 recipes to accelerate the process of learning game design and solving development problems using Unreal Engine. (2015) - Doran, John P, 1988 or 1989-
No abstract available